Evaluation Of Antioxidant, Antidiabetic, Anti-Inflammatory And Anticancer Activities Of Delonix Regia Flower Extracts: Life Sciences-Some Phaemacological activitie Of Delonix Regia Flower Extracts - Benoite. T; Nora Vigasini K (International Journal of Life Science and Pharma Research, 2022)
Non-communicable diseases like diabetes and cancer are the major cause of death worldwide. Various drugs are used for the treatment of these diseases. However, they cause lots of side effects. There is a need for alternate drugs with fewer side effects. Medicinal plants serve as a good source for alternate form of treatment. Therefore, in this study, ethanolic and aqueous extracts of D. regia flowers were evaluated for their antioxidant, antidiabetic, anti-inflammatory and cytotoxic activity to justify its use as a medicinal plant. Total phenol and flavonoid content of the extracts were measured. GC-MS analysis of the extracts were done to investigate the presence of various bioactive compounds. Antioxidant activity was assessed by radical scavenging and reduction assays. Antidiabetic activity was assessed by the ability of extracts to inhibit enzyme alpha amylase. Anti-inflammatory activity was evaluated by membrane stabilization activity. Anticancer activity against MCF-7 and A549 cell lines were measured by the MTT assay.The ethanolic extract contained more phenols (282.940.80 mgGAE/g) and flavonoids (140.912.27 mgQE/g). GC-MS analysis showed the presence of compounds belonging to fatty acids, alkanes, phenols and organic alcohols. The aqueous extract showed strong superoxide radical scavenging activity with a low IC50 of 39.35±0.74 µg/mL. The ethanolic extract showed higher ferric reducing power with an IC50 of 59.65±0.28µg/mL. Ethanolic extract was more potent in inhibiting alpha amylase with a low IC50 value of 47.14±0.6 µg/mL. Ethanolic extract also showed maximum inhibition of 88.86±0.1% against heat induced lysis of cell membrane. Both extracts affected the proliferation of MCF-7 and A549 cell lines at 160 µg/mL. The results of the present study support the use of D. regia flower as a potential source of bioactive phytochemicals and can be used as a plant-based antioxidant, antidiabetic, anti-inflammatory and anticancer agent.